2017
DOI: 10.21909/sp.2017.01.729
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Moderating Role of Social Context on Media Violence Effect in the Case of Peer Aggression among Adolescents

Abstract: The main aim of the study was to examine a potential moderator role of social context in which children are exposed to media (alone, with peers, with parents) in the relationship between the frequency of media use and the frequency of committed peer aggression. The study included 880 elementary school students, which completed the following self-assessment measures: Peer violence among school children questionnaire (Velki, Kuterovac Jagodić, & Vrdoljak, 2012), and Exposure to the media scale (Velki & Kuterovac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…As independent use of the Internet and social media becomes more common, parents can actively monitor usage and equip their adolescent children with skills to engage online responsibly and in a way that maintains their privacy (Padilla-Walker, Coyne, Kroff, & Memmott-Elison, 2018;Sarriera, Abs, Casas, & Bedin, 2012;Velki & Jagodić, 2017).…”
Section: Manuscriptmentioning
confidence: 99%
“…As independent use of the Internet and social media becomes more common, parents can actively monitor usage and equip their adolescent children with skills to engage online responsibly and in a way that maintains their privacy (Padilla-Walker, Coyne, Kroff, & Memmott-Elison, 2018;Sarriera, Abs, Casas, & Bedin, 2012;Velki & Jagodić, 2017).…”
Section: Manuscriptmentioning
confidence: 99%
“…Some research has been done on the impact of online hatred on the frequency of peer aggression in schools. 32 Individuals who exhibit verbal aggression, including acceptance of verbal aggression, may be less sensitive to online hate speech. 2 Some studies have found that high impulsivity is associated with both offline 33 and online 34,35 aggressive behavior and compulsive internet use.…”
Section: Predictors Of Hate Speech Perceptionmentioning
confidence: 99%
“…The effects of the family environment and different types of media environment on adolescent aggressive behavior have been found in a number of studies, e.g. [5][6][7][8], but the parallel impact of these factors, as well as the impact of the social context in which adolescents play video games and watch different media shows, still need to be verified [9]. This outlines the need for systematic research among different types of social, cultural, and family contexts in which children and teenagers learn and are brought up.…”
Section: Introductionmentioning
confidence: 99%